Centro de culto, barrios Larrea y Santa Clara, escala sectorial - Espinosa Estrella, Jorge Andrés (2020)
Two neighborhoods in Quito, ´La Larrea´ and ´Santa Clara´, became the setting of a new urban design project that aimed to regenerate its centrality, residency, and public space. Amongst the elaborated strategies, 21 new urban public buildings were assigned throughout both neighborhoods. One of these buildings, a religious center, was allocated between Avenida Versalles and Calle Alonso de Mercadillo. The purpose of this new religious center was to satisfy the needs of the entire religious population of Quito by the year 2030. The focal religions of the project were Hinduism, Islam, Judaism, Christianity, and Buddhism. Hence, a typology was needed that allowed members of all of these faiths to celebrate their religious practices at the same time. A multifaith typology was the only option to pursue such objectives. The following publications were consulted to create a theoretical framework about multifaith spaces: ´The architecture of multifaith spaces: God leaves the building´ written by Dr. Andrew Crompton; ´Multifaith spaces in public centers in Spain, essay on typology´ written by Dr. Francisco Diez de Velasco; and the digital exhibit ´Multi-faith Spaces´ organized by the Manchester and Liverpool universities. Nevertheless, a specifi c methodology which explains how to design a multifaith space could not be found. In that regard, a typological method was developed to design a multifaith space for Hindus, Muslims, Jews, Christians, and Buddhists. This methodology consists on analyzing the individual characteristics of the mandir, synagogue, ecumenical temple, buddhist temple and mosque; and then synthetize its spaces and organization. This operation is executed twice, first to create ´Religious Prototypes´ and then ´Multifaith Prototypes´. The first phase consisted of using a matrix to typologically analyze three contemporary mandirs, synagogues, ecumenical temples, buddhist temples and mosques. This matrix determined the minimum common spaces between them. Next, a relationship matrix stablished the minimum common distributions. Finally, the results were combined and spatialized using cubes. These are 3-dimensional ´Religious Prototypes´, which were allocated on the northern and southern hemispheres as well as on the equator. For the second phase, this method was used to create a multifaith center. To achieve this, a relationship matrix was used to compare all religious spaces from the ´religious prototypes´ and combine those that shared the same formal and functional characteristics. Then, the protype´s distributions were also combined, avoiding any changes to essential orientational or sequential qualities specific to a particular religion. Finally, the results were combined and spatialized using cubes. These are 3-dimensional ´Multifaith Prototypes´, which were also allocated on the northern and southern hemispheres as well as on the equator. The multifaith center for La Larrea and Santa Clara was designed using the multifaith prototype ´N. A Equatorial´, obtained from the second phase of the project described above. However, an aedicular composition was employed as a concept in order to properly spatialize the project. It is important to mention that the methodology designed for this work can be applied to any building as well as to design a multifaith center. Finally, the research on the form and function of the mandir, synagogue, ecumenical temple, buddhist temple and mosque resulted on a ´family tree´ of typological referents that can similarly be applied to other projects.